Galerucella (Neogalerucella) anserina Ødegaard & Hanssen, sp. nov., a new species of Chrysomelidae (Coleoptera, Chrysomelidae, Galerucinae) from Norway - Ødegaard, Frode; Hanssen, Oddvar (Zootaxa, 2020)
A new chrysomelid beetle, Galerucella anserina Ødegaard & Hanssen, sp. nov., belonging to the Galerucella tenella-group (subgenus Neogalerucella) is described, illustrated and distinguished from similar species within the genus. The type specimens were collected in coastal wetlands in southeastern Norway. The species is associated with Potentilla anserina L. (Rosaceae), and lives sympatrically with the closely related G. tenella (L.).